MENGGAGAS PERADILAN PARTAI POLITIK DAN PEMILU DALAM SISTEM KETATANEGARAAN INDONESIA - Ishak, Ishak (AKTUALITA, 2011)
Rule of law, democracy, political parties and general election arefundamental elements to build a constitutional democracy in Indonesianconstitutional system. Political party has function to put its electedcandidates in public officials through general election system. Therefore,its powers should be restricted by court system and law. Not only, apolitical party court which should be developed, but also a generalelection court in Indonesia constitutional system. Both political party andgeneral election courts should be developed as integrated and systematiccourt system under Constitutional Court.Keywords : judiciary, political parties, elections